Volume 8A: Ocean Engineering 2014
DOI: 10.1115/omae2014-23355
|View full text |Cite
|
Sign up to set email alerts
|

Sloshing Forces on a Tank With Two Compartments, Application of the Pendulum Model and CFD

Abstract: Two different methods, pendulum model and computational fluid dynamics (CFD), to predict the forces on the ship caused by the flooded water are compared against the model test results. Calculations were performed for a tank in forced motions at different frequencies, for which experimental results were available. The tank had a dividing wall with an opening. The overall behaviour of the force time history was well captured with the pendulum model. In particular at lower frequency the agreement of the force ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Damaged ship roll is affected by flooding water exchange. This is implemented in the numerical simulation by means of the flooding law (9,10), where Q is the flow rate:…”
Section: Flooding Law Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Damaged ship roll is affected by flooding water exchange. This is implemented in the numerical simulation by means of the flooding law (9,10), where Q is the flow rate:…”
Section: Flooding Law Modellingmentioning
confidence: 99%
“…Among these, the most accurate are computational fluid dynamics (CFD) approaches, such as the mesh-less technique named smoothed-particle hydrodynamic (SPH) [3,4] and volume of fluid methods (VOF) [5][6][7]. In general, CFD is used intensively for studying sloshing phenomena [8][9][10] and many efforts are made to couple them with the dynamics of a damaged ship in waves [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…where β m is the modal displacement, sloshing force F m is written in 5 × 5 matrix form, and M is the liquid mass matrix considered as solid. Q m is the transfer function between modal response β and the sloshing forces in 5 × 1 matrix form, which can be summarized from equations (15)- (20):…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…On the other hand, it has been observed that if the sloshing is relatively mild, the free surface does not break and the sloshing motion is not chaotic [16], and its motion pattern is analogous to a mechanical system. erefore, many past studies simplify the sloshing liquid into a spring-mass [17,18] or a pendulum [19,20] system. e complication encountered in this approach is that since the mechanical analogy is not based on the fluid theory, it is hard to derive the parameters (mass, stiffness, damping, and natural frequency) of the analogical model directly, unless the tank geometry is simple such as a rectangular tank.…”
Section: Introductionmentioning
confidence: 99%
“…Mitra et al [18,19] developed a coupled algorithm using a hybrid marine control system for ship-motion simulation and a finite element method for nonlinear sloshing. Nakashima et al [20] and Manderbacka et al [21] applied pendulum models to obtain sloshing forces with low computational load. These simplified models, although application may be restricted to some specific limits, can give benchmark data to CFD computations.…”
Section: Introductionmentioning
confidence: 99%